Procoagulant activity in high grade serous ovarian cancer patients following neoadjuvant chemotherapy-The role of the activated protein C pathway. Issue 200 (April 2021) - Ward, Mark P.; Saadeh, Feras Abu; O'Toole, Sharon A.; O'Leary, John J.; Gleeson, Noreen; Norris, Lucy A.
Abstract: Introduction: Ovarian cancer patients are at high risk of thrombosis particularly during chemotherapy treatment however the mechanism is not understood. The aim of this study is to investigate the role of the activated protein C (aPC) pathway in the procoagulant activity observed in ovarian cancer patients undergoing neoadjuvant chemotherapy. Patients and methods: Thrombin generation was determined before and after addition of thrombomodulin (TM) in high grade serous ovarian cancer (HGSOC) patients treated with neoadjuvant chemotherapy (n = 29) compared with HGSOC patients who were chemo naïve (n = 23) and patients with benign tumours (n = 29). Plasma expression of proteins from the aPC pathway was analysed. mRNA expression was determined in endothelial (EA.hy926) and ovarian (OAW42) cell lines following addition of carboplatin and paclitaxel. Results: Lower levels of ETP (p < 0.007; p < 0.003) and peak thrombin (p < 0.0008; p < 0.0018) were found in the neoadjuvant group compared with both chemo naïve and benign groups. Following addition of TM, ETP (p < 0.0005) and peak thrombin (p < 0.0049) were higher in the neoadjuvant group compared with the benign controls indicating an increase in aPC resistance. Increased TM and lower levels of protein S were found in the neoadjuvant group compared with benign controls (p < 0.05; p < 0.003). Factor V levels were increased in the neoadjuvant group compared with the chemo naïve group (p < 0.05). Carboplatin and paclitaxel altered the expression of EPCR and thrombomodulin in OAW42 cells with a modest effect on EA.hy926 cells. Conclusion: Chemotherapy induced procoagulant activity in HGSOC is associated with an alteration in expression of key members of the aPC pathway. This acquired aPC resistance may explain the procoagulant phenotype associated with ovarian cancer patients undergoing chemotherapy. Highlights: Neoadjuvant chemotherapy alters thrombin generation in HGSOC patients. Neoadjuvant chemotherapy promotes resistance to aPC. Neoadjuvant chemotherapy alters plasma expression of members of the aPC pathway. Modified expression of the aPC pathway may explain the procoagulant phenotype.